2021
DOI: 10.3390/microorganisms9050891
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Role of Immune Evasion and Integration of Human Papillomavirus in Oropharyngeal Cancer

Abstract: The incidence of oropharyngeal cancer (OPC) is increasing remarkably among all head and neck cancers, mainly due to its association with the human papillomavirus (HPV). Most HPVs are eliminated by the host’s immune system; however, because HPV has developed an effective immune evasion mechanism to complete its replication cycle, a small number of HPVs are not eliminated, leading to persistent infection. Moreover, during the oncogenic process, the extrachromosomal HPV genome often becomes integrated into the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 95 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…Intriguingly, across species, females tend to develop a stronger innate and adaptive immune response to contagions [51]. Sex difference in immune responses to infectious diseases has been reported [70,71]. HPV infection and associated OPC also showed higher incidence in males when compared with females [1].…”
Section: Discussionmentioning
confidence: 96%
“…Intriguingly, across species, females tend to develop a stronger innate and adaptive immune response to contagions [51]. Sex difference in immune responses to infectious diseases has been reported [70,71]. HPV infection and associated OPC also showed higher incidence in males when compared with females [1].…”
Section: Discussionmentioning
confidence: 96%
“…Disruption of normal cell cycle processes plays an important role in carcinogenesis. 4,[42][43][44] Therefore, it is of great importance to reveal the concrete influence of the CPBisoG gel on the cell cycles of HPV + OSCC. Flow cytometry further revealed that CPBisoG significantly induced S and G2/M arrest and G0/G1 reduce in HPV + OSCC after 24 h (Fig.…”
Section: Inhibitory Efficacy Of the Cpbisog Supramolecular Hydrogel O...mentioning
confidence: 99%
“…The E7 protein degrades retinoblastoma (Rb) family members (i.e., p105, p107, and p130) leading to the release of the E2F transcription factor which promotes gene expression in the S phase, and elicits hyperproliferation. 26 Viral assembly occurs in the maturing squamous epithelium leading to the release of amplified viruses from the terminally differentiated squamous cells. This 3-week process refers to the maturation of a basal cell to the superficial cells.…”
Section: Hpv Life Cyclementioning
confidence: 99%